2020
DOI: 10.1080/17453674.2020.1752017
|View full text |Cite
|
Sign up to set email alerts
|

Higher risk of revision for partial knee replacements in low absolute volume hospitals: data from 18,134 partial knee replacements in the Dutch Arthroplasty Register

Abstract: Background and purpose — Partial knee replacement (PKR) survival rates vary a great deal among registries and cohort studies. These discrepancies can largely be attributed to inappropriate indications of the PKR and low thresholds for revision, but also to the PKR volume. This study used Dutch Arthroplasty Register data to analyze whether absolute PKR or proportional PKR hospital volume is associated with the risk of revision. Patients and methods — 18,134 PKRs were identified in the Dutch Arthropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Studies have shown that these are related to UKA survival. 7,29 Furthermore, there is a notable difference in the usage of cemented and cementless implants between the new and conventional instrumented UKAs, which could possibly bias the revision risk (as cemented implants are associated with a higher revision risk). 30 However, no multicollinearity was found between instrumentation type and fixation type (variance inflation factor <2.5), and with 14% of cementless implants in the conventional instrumented UKAs, our multivariable Cox regression model was expected to adequately adjust for this confounder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that these are related to UKA survival. 7,29 Furthermore, there is a notable difference in the usage of cemented and cementless implants between the new and conventional instrumented UKAs, which could possibly bias the revision risk (as cemented implants are associated with a higher revision risk). 30 However, no multicollinearity was found between instrumentation type and fixation type (variance inflation factor <2.5), and with 14% of cementless implants in the conventional instrumented UKAs, our multivariable Cox regression model was expected to adequately adjust for this confounder.…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not adjust for hospital or surgeon related factors, such as experience and exposure. Studies have shown that these are related to UKA survival [7,29]. Furthermore, there is a notable difference in usage of cemented and cementless implant between the new and conventional instrumented UKA's, which could possibly bias the revision risk (as cemented implant are associated with a higher revision risk) [30].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of KA volume and the availability of a frequently used PKR on the actual PKR use described in this study has not been reported earlier. Many studies report on the effect of PKR volume on outcome, especially with regard to the survival, 7,9,10,18,19 but never on the effect of volume on the actual use and certainly not in combination with the supplier. Previous studies showed a better survival in hospitals with a higher absolute or proportional PKR volume.…”
Section: Discussionmentioning
confidence: 99%
“…This will lead to an increase in number of hospitals using PKR but not necessary to more PKR usage within the hospital, which is needed to achieve optimal PKR results. 710,18 This demands an intrinsic motivation by the surgeon and the hospital to adopt the complete PKR philosophy with applying the strict inclusion criteria for this procedure and achieving sufficient volume. The discrepancy of an even stronger increase in PKR use in larger volume hospitals with a supplier without a frequently used PKR implant in their product range as found in this study, may especially reflect this intrinsic motivation.…”
Section: Discussionmentioning
confidence: 99%